Masa Kemajuan Islam (650-1000 Masehi) - Basri, Muhammad; Salsabila, Dinda; Siregar, Faisa Rahma Safira (Madani: Jurnal Ilmiah Multidisiplin, 2024)
The classical period (650-1250 CE) marked the zenith of Islamic civilization through expansion, integration, and progress, extending the influence of Islam from Spain to India. Under the leadership of caliphs, there was support for advancements in various fields of knowledge. However, the disintegration phase (1000-1250 CE) was characterized by political fragmentation and decline, reaching its climax with the conquest of Baghdad by Hulagu's forces in 1258 CE. Differences in governance systems, democracy during the Khulafaurrasyidin era and monarchy during the Umayyad and Abbasid eras, triggered divisions due to power struggles. In this period, the development of the Islamic community marked the pinnacle through the expansion of influence from Spain to India under caliphal leadership. Despite advancements in various fields of knowledge, the disintegration phase (1000-1250 CE) brought about fragmentation and political decline, culminating in the conquest of Baghdad by Hulagu's forces in 1258 CE. Variances in governance systems, with democracy during the Khulafaurrasyidin era and monarchy during the Umayyad and Abbasid eras, served as the primary catalyst for divisions arising from power competition.